Authorities losing the battle against cybercrime, says UK National Crime Agency. Issue 7 (July 2016) - Unknown
Abstract : The UK's National Crime Agency (NCA) has issued its first report on cybercrime, and admits that it is losing the battle. However, some commentators in the information security industry have criticised the brief report for being too vague and lacking detail.